Service Offshoring – Concepts, Benefits and Risks (Revista ADMPG, 2019)
Offshoring has two different concepts that one of them is part of an outsourcing and another that independently of the services to be supplied by the own company or external provider what is important to highlight is that services will be provided from a foreign country. In this paper we present a theoretical review on the concepts of offshoring and its implications, benefits and issues for the parties involved in the process. In other words, the key elements that should be analyzed when making the decision to offshore considering the location, benefits and risks.